A comparative study of corrosion behavior of S-phase with AISI 304 austenitic stainless steel in H2S/CO2/Cl- media. (15th July 2021) - Li, Longyi; Yan, Jing; Xiao, Jie; Sun, Lan; Fan, Hongyuan; Wang, Jun
Highlights: Corrosion behaviors of S-phase and austenitic stainless steel in H2 S/CO2 /Cl − media were evaluated after long-term immersion. The types and effects of corrosion products were analyzed at various times. The Fe3 O4 layer can effectively block corrosive ions. The presence of the S-phase layer reduced the corrosion rate of AISI 304 steel by 89.8 %. Abstract: S-phase was introduced on stainless steel surface by low-temperature liquid oxy-nitriding and its influence on the corrosion behavior has been explored through surface analysis and weight-loss method. The results indicated that the S-phase layer can significantly improve the corrosion resistance of austenitic stainless steels in H2 S/CO2 /Cl − simulated solutions, which was proved by lower corrosion rate, surface, and cross-sectional topography after corrosion. This improvement can be attributed to the fact that the Fe3 O4 layer blocking the sulfur-containing medium and the consumption of H + by the active nitrogen atoms, making it difficult for the corrosive medium to penetrate the steel.